Seizing Power : the Grab for Global Oil Wealth. - Slater, Robert (Bloomberg., 2010)
Praise for Seizing Power: The Grab for Global Oil Wealth. "In Seizing Power, Robert Slater takes a whole new slant on the oil issue, offering for the first time an analysis of how the ongoing oil crisis could trigger increased turbulence, even violence between the new breed of petroaggressors. He explains in clear language with lots of powerful anecdotes how a wide range of 'second tier' countries in Africa and Asia are suddenly competing for and acquiring vast oil wealth and power. A must-read for those wondering how these new oil actors are reacting to a much tougher oil environment. & q.